2012
DOI: 10.1007/s11695-012-0828-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Bypass Versus Laparoscopic Sleeve Gastrectomy as a Definitive Surgical Procedure for Morbid Obesity. Mid-Term Results

Abstract: There is a similar short- and mid-term weight loss and 1-year comorbidity improvement or resolution between LRYGB and LSG, although minor complication rate is higher for LRYGB. Results of LSG as a single procedure need to be confirmed after a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 32 publications
5
46
1
6
Order By: Relevance
“…In the study by Vidal and colleagues, 14 minor complications were reported in 5 (4.4%) patients: urinary tract infection (n = 2), pseudomembranous colitis (n = 1), hypertensive crisis (n = 1) and subphrenic abscess (n = 1). Major complications were reported in 5 (4.4%) patients: gastric leak (n = 2), bleeding from the port site (n = 2) and acute myocardial infarction resulting in death (n = 1).…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Vidal and colleagues, 14 minor complications were reported in 5 (4.4%) patients: urinary tract infection (n = 2), pseudomembranous colitis (n = 1), hypertensive crisis (n = 1) and subphrenic abscess (n = 1). Major complications were reported in 5 (4.4%) patients: gastric leak (n = 2), bleeding from the port site (n = 2) and acute myocardial infarction resulting in death (n = 1).…”
Section: Discussionmentioning
confidence: 98%
“…Large observational studies and RCTs ( n  > 50) as well as a meta-analysis show either no differences between procedures [9] or a greater rate of one or more of the following for GB: minor complications, longer hospital stay, and longer operative time [8, 10, 12, 14, 16, 1824]. …”
Section: Introduction/purposementioning
confidence: 99%
“…Consequently, LSG has been proposed as an effective alternative to laparoscopic Roux-en-Y gastric bypass and is associated with a relatively shorter operating time and fewer complications, with comparable clinical outcomes [4,[19][20][21][22][23][24]. Many other studies have demonstrated that LSG is a safe and feasible technique resulting in a short operating time and short length of hospitalization [25]. Still, postoperative complications associated with LSG have been reported, including leaks and bleeding [26].…”
Section: Introductionmentioning
confidence: 99%